Community development and livestock promotion in rural Nepal:effect on child health and growth. - Joshi, Mahesh Prasad. (Tufts University. Tisch Library., 2016)
This presentation explores the effects and impacts of Heifer activities on the health and nutrition status of Nepali children, then makes suggestions for further studies. Keywords: Scientific Symposium, Heifer International.; Nutrition School: NIL Symposium Presentations, 2013.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy